Dosage Optimization of Polypropylene Fiber for Strength Enhancement of Cementitious Composites - Irshidat, Mohammad R.; Al Nuaimi, Nasser; Salim, Soheb; Rabie, Mohamed (Proceedings of the International Conference on Civil Infrastructure and Construction (CIC), 2020)
Concrete is the most commonly used materials for construction in Qatar as well as in the world. Exposure to sever environmental conditions causes physical deterioration of concrete structures and significantly affect the concrete’s strengths and modulus of elasticity. In the last decades, many improvements had been made in concrete technology. Most of these improvements focused on the weak point of concrete, which is tensile strength enhancement. One possible method to improve the tensile strength of cementitious composites is incorporation of fibers in the mix. Polypropylene fiber is widely used for this purpose due to their corrosion resistance and relatively low cost. Polypropylene fibers are usually incorporated in cement mortar to control cracks propagation thus enhance its tensile and flexural properties. This research focuses on Polypropylene fiber dosage optimization for strength enhancement of cementitious composites. Four dosages of Polypropylene microfibers; 0%, 0.05%, 0.1%, and 0.2% by weight of cement; were added into cement mortar to explore the optimum dosage that can lead to big enhancement in mechanical strengths of cementitious composites. The mechanical strengths were investigated in terms of compressive and flexural strengths. The results revealed that adding small amount of Polypropylene microfibers could enhance the compressive and flexural strengths of cement mortar. The maximum enhancement in the compressive and flexural strengths was equal to 26% and 19% and was achieved in the case of adding 0.1% and 0.05% by weight of cement, respectively.